A)
{4a+2b=10
5a-2b=-10

b)
-2x+y=4
2x+2y=2

c)
2x+y=5
2x+y=7

d)
5x-2y=8
10x-4y=16

e)
5x-y=1,5
3x+6y=4,2

f)
5x-y=7
2(x+1)=2y

g)
6x+7y=0
-2x+3y=o

h)
x+4y=1
x-8y=-1

i)
8x-6y=10
7x+y=5

j)
5x-5y=2,5
7y+3x=14,5

k)
7x+7y=21
2x+5y+8=14

l)
3x+y=11
2x-y=2

ł)
4(x-2)-(y-2)=1
10x-2y=18

m)
2x-4(y+1)=10
2(x+3)-(1-y)=9

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-19T17:00:57+01:00
A)
{4a+2b=10
5a-2b=-10

9a=0 /:9
a=0

b)
-2x+y=4
2x+2y=2

3y=6 /:3
y=2

2x+2y=2
y=2

2x+2*2=2
y=2

2x+4=2
y=2

2x=2-4
y=2

2x=-2/:2
y=2

x=-1
y=2

c)
2x+y=5 I * (-1)
2x+y=7

-2x-y=-5
2x+y=7

0=2

d)
5x-2y=8 I * (-2)
10x-4y=16

-10x+4y=-16
10x-4x=16

0=0

e) 5x-y=1,5 I *6
3x+6y=4,2

30x-6y=9
3x+6y=4,2

33x=13,2 /:33
x=0,4

3x+6y=4,2
x=0,4

3*0,4++6y=4,2
x=0,4

1,2+6y=4,2
x=0,4

6y=4,2-1,2
x=0,4

6y=3 /;6
x=0,4

y=0,5
x=0,4

f)
5x-y=7
2(x+1)=2y

5x-y=7
2x+2=2y

5x-y=7 I*(-2)
2x-2y=-2

10x+2y=14
2x-2y=-2

12x=12 /:12
x=1

2x-2y=-2
x=1

2*1-2y=-2
x=1

2-2y=-2
x=1

-2y=-2+2
x=1

-2y=0 /:(-2)
x=1

y=0
x=1

g)6x+7y=0
-2x+3y=o I*3

6x+7y=0
-6x+9y=0

16y=0 /:16
y=0

6x+7y=0
y=0

6x+7*0=0
y=0

6x+0=0
y=0

6x=0 /;6
y=0

x=0
y=0

h)x+4y=1
x-8y=-1

x=1-4y
x-8y=-1

x=1-4y
1-4y-8y=-1

x=1-4y
-4y-8y=-1-1

x=1-4y
-12y=-2/:(-12)

x=1-4y
y=1/6

x=1-4*1/6
y=1/6

x=1-2/3
y=1/6

x=-1/3
y=1/6

i)
8x-6y=10
7x+y=5 I*6

8x-6y=10
42x+6y=30

50x=40 /:50
x=0,8

8x-6y=10
x=0,8

8*0,8-6y=10
x=0,8

6,4-6y=10
x=0,8

-6y=10-6,4
x=0,8

-6y=3,6 /:(-6)
x=0,8

y=0,6
x=0,8

j)
5x-5y=2,5 I*3
7y+3x=14,5 I*(-5)

15x-15y=7,5
-15x-35y=72,5

-50y=80 /:(-50)
y=-1,6

15x-15y=7,5
y=-1,6

15x-15*(-1,6)=7,5
y=-1,6

15x+24=7,5
y=-1,6

15x=7,5-24
y=-1,6

15x=-16,5 /:15
y=-1,6

x=-1,1
y=-1,6

k) 7x+7y=21
2x+5y+8=14

7x+7y=21
2x+5y=14-8

7x+7y=21 I*5
2x+5y=6 I*(-7)

35x+35y=105
-14x-35y=-42

21x=63 /:21
x=3

35x+35y=105
x=3

35*3+35y=105
x=3

105+35y=105
x=3

35y=105-105
x=3

35y=0 /:35
x=3

y=0
x=3


l)
3x+y=11
2x-y=2

5x=13 /:5
x=2,6

3x+y=11
x=2,6

3*2,6+y=11
x=2,6

7,8+y=11
x=2,6

y=11-7,8
x=2,6

y=3,2
x=2,6

ł)
4(x-2)-(y-2)=1
10x-2y=18

4x-8-y+2=1
10x-2y=18

4x-y=1+8-2
10x-2y=18

4x-y=7 I*(-2)
10x-2y=18

-8x+2y=-14
10x-2y=18

2x=4 /:2
x=2

10x-2y=18
x=2

10*2-2y=18
x=2

20-2y=18
x=2

-2y=18-20
x=2

-2y=-2 /:(-2)
x=2

y=1
x=2

m)
2x-4(y+1)=10
2(x+3)-(1-y)=9

2x-4y-4=10
2x+6-1+y=9

2x-4y=10+4
2x+y=9-6+1

2x-4y=14
2x+y=4 I*4

2x-4y=14
8x+4y=14

10x=28 /:10
x=2,8

2x-4y=14
x=2,8

2*2,8-4y=14
x=2,8

5,6-4y=14
x=2,8

-4y=14-5,6
x=2,8

-4y=8,4 /:(-4)
x=2,8

y=-2,1
x=2,8






1 5 1
2009-12-19T17:01:30+01:00
A)
{4a+2b=10
5a-2b=-10

4a+5a=20
9a=0
a=0
2b=10
b=5

------------------------
b)
-2x+y=4
2x+2y=2

3y=6
y=2

2x=2-4
2x=-2
x=-1
------------------------
c)
2x+y=5
2x+y=7

ten przykład jest zły, bo 5 nie równa się 7 // x=0 y=0
------------------------
d)
5x-2y=8 <*2
10x-4y=16

-10x+4y=-16
10x-4y=16

------------------------
e)
5x-y=1,5 >*6
3x+6y=4,2

30x-6y=9
3x+6y=4.2

33x=13.2
x=2.5
3*2.5+6y=4.2
6y=4.2-7,5
6y=-3.3
y= -0.55

------------------------
f)
5x-y=7
2(x+1)=2y

5x-y=7
2x+2=2y

5x-y=7 <*-2
2x-2y=-2

-10x+2y=-14
2x-2y=-2

-8x=-16
x=2

2x+2=2y
6=2y
y=3

------------------------
g)
6x+7y=0
-2x+3y=0 <*3

6x+7y=0
-6x+9y=0

16y=0
y=0
x=0

------------------------
h)
x+4y=1 <*-1
x-8y=-1

-x-4y=-1
x-8y=-1
-12y=-2
y=1/6
x=1-4y
x=1-4/6
x=2/6 = 1/3

------------------------
i)
8x-6y=10
7x+y=5 <*6

8x-6y=10
42x+6y=30

50x=40
5x=4
x=5/4
y=5-7y
y=5-8,75
y=(-3,75)

j)
5x-5y=2,5 <*-3
7y+3x=14,5 <*5

15y-15x=7.5
35y+15x=72.5
50y=80
y=8/5 = 1,6
5x=2.5+5y
5x=10.5
x=2.1

------------------------
k)
7x+7y=21 <*(-2)
2x+5y+8=14 (*7)

-14x-14y=-42
14x+35y=42 <(jakby co 6*7)

21y=0
y=0

14x+0=42
14x=42
x=3

------------------------
l)
3x+y=11
2x-y=2

5x=13
x=2,6

ł)
4(x-2)-(y-2)=1
10x-2y=18

4x-8-y+2=1
10x-2y=18

4x-y=5 <*(-2)
10x-2y=18

-8x+2y=(-10)
10x-2y=18

2x=8
x=4

10x-2y=18
2y=10x-18
2y=40-18
2y=22
y=11
------------------------
m)
2x-4(y+1)=10
2(x+3)-(1-y)=9

2x-4y+4=10
2x+6-1+y=9

2x-4y=6
2x+y=4 <*(-1)

2x-4y=6
-2x-y=-4

-5y=2
y=(-0.4)

2x=6+4y
2x=6-1.6
2x=4.4
x=2.2